2011
DOI: 10.1001/archinternmed.2010.492
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Concentration and Correlates of Nursing Home Closures: 1999-2008

Abstract: Background While demographic shifts project an increased need for long-term care for an aging population, hundreds of nursing homes close each year. We examine whether nursing home closures are geographically concentrated and related to local community characteristics such as the racial and ethnic population mix and poverty. Methods National Online Survey Certification and Reporting data were used to document cumulative nursing facility closures over a decade, 1999 through 2008. Census 2000 zip code level de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 18 publications
1
53
0
1
Order By: Relevance
“…Yet between 1999 and 2008, nearly 16 percent of all nursing homes certified by Medicare or Medicaid closed, resulting in a net loss of more than 5 percent of beds. 13 More important, these closures were concentrated in minority and poor communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet between 1999 and 2008, nearly 16 percent of all nursing homes certified by Medicare or Medicaid closed, resulting in a net loss of more than 5 percent of beds. 13 More important, these closures were concentrated in minority and poor communities.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies of nursing home closures have found, the numbers of closures are higher in communities characterized by high rates of poverty, higher proportions of racial and ethnic minority residents, and very few new nursing home openings. 13 The geographic distribution of newer forms of long-term care is still largely unknown; whether such services are moving into communities that have lost nursing homes is unclear.…”
Section: The Changing Long-term Care Landscapementioning
confidence: 99%
“…Extending the time that older adults remain in the community setting could decrease personal and public financial burden (H. S. Kaye, Harrington, & LaPlante, 2010), and alleviate the projected shortage of available long-term care placements (Feng et al, 2011). Prolonging care in the community may also decrease the risk of negative outcomes for older adults that are associated with placement, such as loneliness (Pinquart & Sörensen, 2001), and malnutrition (Kaiser et al, 2010).…”
mentioning
confidence: 99%
“…In the decade after introduction of SNF prospective payment system (PPS), the number of hospital-based SNFs dropped from about 2,500 to about 1,000, since hospital-based SNF costs were generally much higher than SNF PPS rates [24] . As a result, hospitals and health systems will cautiously pursue a full integration post-acute strategy.…”
Section: Mechanisms To Control the Total Cost Of Carementioning
confidence: 99%